A Discussion of Techniques to Mitigate Non-Linearity in Scale Factor Within a Linear Accelerometer Under Capacitive Drive. - Soni, Krishna M. (2014)
Abstract: The development of highly accurate, strategic-grade sensors is integral for the development of Inertial Navigation Systems (IMUs). Currently, sensors which make up IMUs are limited by bandwidth, size, and stability. The Zero Force Accelerometer (ZFA) aims to exceed these specifications as the next generation of high precision sensor. It is necessary then to mitigate any source of error in order to increase the integrity of the device. Small displacement error, temperature drift and variable analog inputs call for an in-situ scale factor calculation, but at a cost. In particular, a g-dependent term was observed, propagating to 61,599 ppm/g. A new algorithm was proposed exploiting changing parameters on the fly, and calculating and combining two scale factor measurements to eliminate the g-dependency. The results showed two orders of magnitude improvement of scale factor error (311.43 ppm/g), but still does meet strategic-grade specifications, so further study is desired.